A comparative study on drillability of Inconel 625 alloy fabricated by wire arc additive manufacturing. (3rd March 2023) - Ceritbinmez, Ferhat; Günen, Ali; Gürol, Uğur; Çam, Gürel
Abstract: In recent years, the cost-effective wire arc additive manufacturing (WAAM) method is increasingly replacing traditional production methods for Ni-based superalloys. However, the effect of high heat input and elemental segregation in the WAAM method on machinability has not yet been adequately investigated. For this purpose, drilling of wrought and WAAM Inconel 625 samples with thermal (i.e., die-sinking micro-EDM and micro-EDM) and mechanical drilling techniques (i.e., orbital and conventional drilling) was investigated in this study. It was observed that thermal drilling methods formed a white layer with a thickness of 20-25 μm and 35-50 μm in the cross-section of wrought and WAAM specimens, respectively, while no white layer was formed in the mechanical methods. The average surface roughness of the inside hole, Ra, obtained in the conventional drilling process has improved by 46.15 %, 94.62 %, and 92.82 %, compared to the orbital, die-sinking, and micro-EDM methods, respectively. Because the drill cutting form and helix angle used in this method facilitated chip evacuation. The best surface roughness was obtained respectively by conventional (0.27–029), orbital (0.51–0.53), die-sinking (4.54–5.88), and micro-EDM drilling (3.54–4.25) methods. In addition, a larger kerf angle is obtained in the WAAM sample compared to the wrought one due to higher residual stress and higher dislocation density in the WAAM alloy. On the other hand, the higher hardness value of WAAM samples provided better surface quality in mechanical drilling methods than wrought material. An increase in surface hardness values up to 25 μm from the surface was detected due to the recast layer formed in thermal drilling methods and the strain hardening occurring on the surface in mechanical drilling methods.